Interplay of Honor and Shame: An Analytical Study of Selected Non-Fictional Writings of Jaswinder Sanghera and Deepa Narayan: Reclaiming Womanhood: A Critical Analysis of Jaswinder Sanghera and Deepa Narayan's Non-Fictional Writings (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Within the walls of their own minds women are being subjected to continuous torture trauma for a variety of reasons. They yearn to be free from exploitation, victimization, injustice and all such evils that challenge their existence. For a woman, freedom is not a matter of having but a matter of being, a state of mind which gives her the liberty to transcend all kinds of barriers that the social order, religion, caste, gender and culture impose on her. She longs to carve a niche for herself in a world of mislaid identities which seeps into the dominance of the males and lowers the status of women though history gives evidence to show that women were not only intellectually at par with men but were also valued for their individualism. This study is structured under the broad framework of honor and shame as set in the minds of women through two non-fictional works written by Jaswinder Sanghera and Deepa Narayan thereby questioning their identity as well as existence in order to reclaim and rename womanhood and question the very basis of it.